2015
DOI: 10.1039/c5cc05785j
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive supramolecular vesicles assembled by water-soluble pillar[5]arene and a BODIPY photosensitizer for chemo-photodynamic dual therapy

Abstract: Supramolecular vesicles which can successfully encapsulate DOX and exhibit rapid drug release in a low-pH environment are constructed based on the host-guest interaction of water-soluble pillar[5]arene and a BODIPY derivative. They show remarkable combination of chemo- and photodynamic activities, suggesting a promising drug nanocarrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(72 citation statements)
references
References 48 publications
0
72
0
Order By: Relevance
“…Therefore, in the following work, a BODIPY-functionalized quaternary ammonium derivative G9 was synthesized, which acted as a photosensitizer and also as a guest to form a supramolecular amphiphile with WP5 based on host-guest interactions (Figure 7). [34] The resulting amphiphile formed from WP5 and G9 could further self-assemble into supramolecular vesicles, which could successfully encapsulate the chemotherapy drug DOX with good loading efficiency, and the formed DOX-loaded vesicles showed effective and rapid release of DOX in an acidic environment, making such systems promising candidates for controlled drug release. Moreover, the obtained supramolecular vesicles had good biocompatibility and the DOX-loaded vesicles could localize well in lysosomes and showed a remarkable combination of chemo-and photodynamic activities against A549 cancer cells upon irradiation with red light, suggesting that this is a potential DDS for chemo-photodynamic dual therapy.…”
Section: Pillararene-based Stimuli-responsive Sddss For Chemo-photodymentioning
confidence: 99%
“…Therefore, in the following work, a BODIPY-functionalized quaternary ammonium derivative G9 was synthesized, which acted as a photosensitizer and also as a guest to form a supramolecular amphiphile with WP5 based on host-guest interactions (Figure 7). [34] The resulting amphiphile formed from WP5 and G9 could further self-assemble into supramolecular vesicles, which could successfully encapsulate the chemotherapy drug DOX with good loading efficiency, and the formed DOX-loaded vesicles showed effective and rapid release of DOX in an acidic environment, making such systems promising candidates for controlled drug release. Moreover, the obtained supramolecular vesicles had good biocompatibility and the DOX-loaded vesicles could localize well in lysosomes and showed a remarkable combination of chemo-and photodynamic activities against A549 cancer cells upon irradiation with red light, suggesting that this is a potential DDS for chemo-photodynamic dual therapy.…”
Section: Pillararene-based Stimuli-responsive Sddss For Chemo-photodymentioning
confidence: 99%
“…In this construct, watersoluble pillar [5]arene was used as a host (carrier) for a diiodo-BODIPY derivative that contains a quaternary ammonium tail. [25] Supramolecular vesicles (pseudorotaxane) formed with pillar [5]arene and the modified dye are highly stable under physiological conditions but undergo disassembly in an acidic environment to release the dye. In a proof of principle study, the vesicles were found to be cytotoxic only to A549 cancer cells under 690 nm irradiation, suggesting that they disassemble Adv.…”
Section: Low Ph Of Tumor Microenvironments Activates Cancerspecific Imentioning
confidence: 99%
“…Noncovalent interactions can also endow nanomaterials with tumor‐specific sensitivity and controllable photoactivity . Meng et al developed supramolecular vesicles by using a BODIPY‐functionalized quaternary ammonium derivative (guest) with a water‐soluble pillar[5] arene (WP5, host) ( Figure a,b) . The binding affinity for such a supramolecular system (WP5⊃G) was mainly driven by the cooperative electrostatic and hydrophobic interactions.…”
Section: Bodipy Nano‐photosensitizers For Pdtmentioning
confidence: 99%
“…c) Vesicles and DOX‐loaded vesicles against A549 cancer cells upon irradiation (l = 690 nm, 1.5 J cm −2 ) and in the dark, respectively. All panels reproduced with permission . Copyright 2015, The Royal Society of Chemistry.…”
Section: Bodipy Nano‐photosensitizers For Pdtmentioning
confidence: 99%